Assessing redistribution of muscle innervation zones after spinal cord injuries - Li, Xiaoyan; Lu, Zhiyuan; Wang, Inga; Li, Le; Stampas, Argyrios; Zhou, Ping (Journal of electromyography and kinesiology, 2021)
This study aimed to examine the redistribution of neuromuscular junctions or innervation zones (IZs) after spinal cord injuries (SCI). Fifteen able-bodied subjects and 15 subjects with SCI (American Spinal Injury Association Impairment Scale A to D), participated in the study. Surface electromyography (EMG) signals were collected from the biceps brachii muscle by a customized linear electrode array when subjects generated maximal isometric voluntary contractions. The Radon transform was applied to detect the IZ locations in the multiple channel surface EMG signals which were differentiated between consecutive channels. The distribution of IZs was compared between the SCI and control groups using the student-t test. Statistical analysis disclosed a significantly wider range of IZs in the SCI group compared with the control group (SCI: 3.83 ± 1.32 IED, control: 2.83 ± 0. 87 IED, IED: inter-electrode distance, p < 0.05). No remarkable shifts of the center of the distribution were observed between the two groups (SCI: 9.23 ± 2.35 IED, control: 8.53 ± 2.33 IED, p = 0.42). Changes of IZ distribution in the paralyzed muscles could be associated with the complex neuromuscular reorganization after the SCI.